Research Freedom and Access to Knowledge in Archaeological Research on Human Remains: Legal and Extra-Legal Perspectives - Mazur, Paweł; Nowak, Ewa (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Present-day bioarchaeology of human remains has a complex, normative foundations, and this results in a nearly paradigmatic shift in research conducted in that discipline of science. This article first introduces the manifold non-scientific significance of human remains and mortuary sites and the essentials of bioarchaeological research as well. It subsequently examines the concept of research freedom in the context of international and domestic regulations. Each state regulates bioarchaeological research distinctly. The article outlines a diplomatic pathway for undertaking research abroad. We then examine (de)colonial, indigenous, religious, and political contexts in which extra-legal regulations on the study of human remains also gain validity. This leads to a normative pluralism, the sources and justification of which we analyse and examplify. Such a pluralism unveils the deficits of positive legal regulation in the various contexts of discussed research. Our article is to support researchers in dealing with normative challenges – legal and extralegal – when it comes to undertaking research on human remains.